Genetic Diversity in White- and Orange-Fleshed Sweetpotato Farmer Varieties from East Africa Evaluated by Simple Sequence Repeat Markers - Tumwegamire,S.; Rubaihayo, P. R.; Kapinga, R.; Mwanga, R. O. M.; Grüneberg, W. J. (Crop Science, 2011)
Sweetpotato [Ipomoea batatas (L.) Lam] farmer varieties are still the backbone of production and breeding programs in Sub-Sahara Africa. Usually, farmer varieties in Sub-Sahara Africa are white- or cream-fleshed sweetpotato (WFSP), but recently orange-fleshed sweetpotato (OFSP) were found in East Africa. The objective of the study was to characterize WFSP and OFSP germplasm from East Africa. Eighty-five East African farmer varieties (29 OFSPs and 56 WFSPs) and seven varieties of non-African origin as check clones were analyzed for diversity using 26 simple sequence repeat (SSR) markers. A total of 158 alleles were scored with an average of 6.1 alleles per SSR loci. The mean of Jaccard's similarity coefficients was 0.54. The unweighted pair group method analysis (UPGMA) revealed a main cluster for East Africa germplasm at a similarity coefficient of 0.52. At a similarity coefficient of about 0.55 subclusters within the East African germplasm were observed, but these were neither country nor flesh color specific. Analysis of molecular variance (AMOVA) found a significant difference between East African and non-African germplasm and a nonsignificant difference between OFSP and WFSP germplasm. In conclusion, the East African germplasm appears to be distinct from non-African germplasm, and OFSP and WFSP farmer varieties from East Africa are closely related. Orange-fleshed sweetpotato farmer varieties from East Africa might show similar adaptation to Sub-Sahara African environments as WFSP and a big potential in alleviating vitamin A deficiency.